Language Variations of Conversation in Buying and Selling Transactions at Dempo Permai Market, Pagar Alam City: Variasi Bahasa Percakapan dalam Transaksi Jual Beli di Pasar Dempo Permai Kota Pagar Alam - Wiransyah, Restu; Pebrianti, Ike Tri; Aristya, Irma Sendy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Language serves not only as a medium for communication but also as a reflection of social identity and cultural interaction. Specific Background: Traditional markets offer a unique linguistic setting where diverse speakers engage in dynamic, real-time exchanges. Knowledge Gap: Despite previous studies on market language use, the role of language variation as a strategic communication tool in economic interactions remains underexplored, particularly in Pagar Alam City. Aims: This study aims to identify speaker-based language variations—idiolect, dialect, sociolect, and chronolect—in transactional conversations at Dempo Permai Market and to assess their communicative and cultural functions. Results: Findings from 37 informants reveal multilingual interactions involving Bahasa Indonesia, Besemah, Javanese, Palembang Malay, and youth slang. These variations are influenced by speakers' age, education, and social status and serve to build rapport, facilitate negotiation, and reflect regional identity. Novelty: This research uniquely connects language variation to strategic communication and buyer-seller relationship-building in traditional economic settings. Implications: Insights from this study can inform communication training for market vendors, sociolinguistic curriculum development, and local language preservation policies, emphasizing the economic and cultural value of linguistic diversity in traditional marketplaces.Highlight : Language in traditional markets shows variation based on speakers' age, background, and region. Code-switching and dialect use serve as communication strategies in transactions. Local language reflects identity and supports sustainable traditional market development. Keywords : Language Variation, Buying and Selling Transactions, Traditional Market, Sociolinguistics, Pagar Alam